2011
DOI: 10.3917/soco.084.0151
|View full text |Cite
|
Sign up to set email alerts
|

Genre, classe, nationalité et accès des femmes aux espaces publics à Riyad

Abstract: La capitale de l’Arabie Saoudite, Riyad, est caractérisée par une ségrégation de genre très poussée et qui s’applique plus strictement aux Saoudiens qu’aux non-Saoudiens. L’article montre comment l’accès de certaines Saoudiennes à des espaces publics contribue à renforcer et/ou à recomposer des hiérarchies sociales qui articulent genre, classe et nationalité. Si des attentes fort contraignantes pèsent sur leurs conduites en tant que Saoudiennes par opposition aux résidentes étrangères, elles parviennent en exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 28 publications
0
2
0
3
Order By: Relevance
“…We found that the participants were satisfied and agreed on the factors of this domain although the women history of mobility freedom had sensational events [41]. In the book “Gender, Class, Nationality, and Women’s Access to Public Places in Riyadh ” Saudi women faced obstacles in many aspects of their lives that hindered their empowerment and independence [42]. Examples of reasons behind the almost complete absence of women in public places mentioned by the author included; a) women driving was prohibited in the past b) the lack of public transportation, c) the financial cost in the case of hiring a driver, d) lack of anti-harassment laws, which is restricting the mobility freedom [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the participants were satisfied and agreed on the factors of this domain although the women history of mobility freedom had sensational events [41]. In the book “Gender, Class, Nationality, and Women’s Access to Public Places in Riyadh ” Saudi women faced obstacles in many aspects of their lives that hindered their empowerment and independence [42]. Examples of reasons behind the almost complete absence of women in public places mentioned by the author included; a) women driving was prohibited in the past b) the lack of public transportation, c) the financial cost in the case of hiring a driver, d) lack of anti-harassment laws, which is restricting the mobility freedom [42].…”
Section: Discussionmentioning
confidence: 99%
“…In the book "Gender, Class, Nationality, and Women's Access to Public Places in Riyadh " Saudi women faced obstacles in many aspects of their lives that hindered their empowerment and independence [42]. Examples of reasons behind the almost complete absence of women in public places mentioned by the author included; a) women driving was prohibited in the past b) the lack of public transportation, c) the financial cost in the case of hiring a driver, d) lack of anti-harassment laws, which is restricting the mobility freedom [42]. Limited access to transportation can increase women's "hidden" barriers to the participation in the labor market and negatively affect their access to other services such as education or health, and ultimately reduce women's empowerment [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Compte tenu du poids des normes de genre, religieuses et sociales dominantes (Le Renard, 2011a, 2011b en Arabie saoudite -notamment en ce qui a trait au rapport à l'espace (sexué) et aux mobilités -, mon enquête à Riyad a supposé, de bout en bout, des précautions spécifiques et, après coup, un protocole d'enquête peu canonique (Bouillon, Fresia, & Tallio, 2005). Sur ce terrain, mon type occidental, mes traits biologiques ou identitaires tels que mon âge, mon sexe ou genre et mon prénom chrétien, ont constitué tantôt un privilège, tantôt un discrédit.…”
Section: Introductionunclassified
“…L'étude de leurs modes de consommation, de leur volonté de s'affranchir des logiques traditionnelles, de leur désir d'émancipation -aspiration à un mode de vie plus aisé (LeBlanc & Soares 2015) -et d'ascension sociale par les études supérieures notamment (Therborn 2012), permet d'analyser, au cas par cas, les signes de distinction de ces populations : travail des femmes, scolarisation, urbanisation, catégories de métiers, positionnements politiques, biens de consommation, mobilités régionales et internationales, entre autres. , politiques, de genre, etc., n'y sont que très peu étudiées en termes de classes(Le Renard 2011 ;Shafik & Battesti 2011). Le système de castes (Gaborieau 1986 ; Delage 2011) leur est habituellement préféré, notamment là où les musulmans représentent une minorité (Gilquin 2010).Les contributions de ce numéro se distinguent de cette littérature.…”
unclassified